La historia oral y el fortalecimiento de la cultura ambiental en la cuenca del río Morote, Guanacaste, Costa Rica. Un estudio de caso: La mansión de Maceo - Cruz Chaves, Carlos (Revista de historia., 2015)
The article exposes the methodology and results of the investigation and extension that have been realized in the subprogram for the integral management of Morote hydrographic basin, Guanacaste, Costa Rica. Through local history method starts the systematization of the historic knowledge and local collective memory about the origin of La Mansión de Maceo and the cultural use of Morote River. The study is grounded on bibliographic information, newspapers located at the National Library and primary source from National Archive. Also it has a component of oral history based on group and personal interviews, workshop and field trip.